Correction: BILBO1 is a scaffold protein of the flagellar pocket collar in the pathogen Trypanosoma brucei. - Célia Florimond; Annelise Sahin; Keni Vidilaseris; Gang Dong; Nicolas Landrein; Denis Dacheux; Anna Albisetti; Edward H Byard; Mélanie Bonhivers; Derrick R Robinson (PLoS Pathogens, 2015)
[This corrects the article DOI: 10.1371/journal.ppat.1004654.].